Prognosis of malignant lymphoma in dogs and correlation to thymidine kinase (TK1) : a retrospective study - Falk, Elin (SLU/Dept. of Clinical Sciences (until 231231), 2018)
Malignant lymphoma is the most common canine hematopoetic neoplasm, with an estimated incidence rate of 20-100 cases per 100,000 dogs. Malignant lymphoma can arise in any organ containing lymphoid tissue and is characterized by malignant proliferation of lymphoid cells. Lymphomas most commonly occur in middle-age to older dogs, where the age category six to ten years seems to be predisposed. Although any dog breed can be affected, middle-sized to large dog breeds are overrepresented. There are many similarities between canine lymphoma and human non-Hodgkin lymphoma (NHL) and the canine lymphoma serves as a good large-animal model for the human NHL. Thymidine kinase is a cellular enzyme involved in the salvage pathway of DNA-synthesis. Thymidine kinase 1 (TK1) is regulated by the cell cycle and is located in the cytoplasm. Moreover, TK1 is converting thymidine to thymidine monophosphate, and is related to DNA replication and cell proliferation, which makes it possible to use as a proliferation marker in malignant tumors. Thymidine kinase 1 activity is present in the early S-phase of cell division in normal cells. However, in abnormal cells the activity of TK1 is often much higher. Previous studies have shown that TK1 is useful in diagnosis and prognosis in humans and dogs with malignant lymphoma. The challenging area with canine lymphoma is rarely to set the diagnosis, but to predict the prognosis and monitor the remission status in an objective way. Moreover, it is a challenge to detect relapse in treated patients. The purpose of the study was to compare initial blood parameters, for example TK and CRP, with clinical symptoms, clinical stage and prognosis. The aim was to improve the prognostication and thereby be able to select the right patients for further treatment. The results of the study showed that there were no significant correlation between a higher initial TK value and a shorter survival time and poorer prognosis. Neither could a high CRP level, hypercalcemia, anemia, a high clinical stage, a T-cell lymphoma, B symptoms nor a high grade tumor be correlated to a shorter survival time. The most important thing for a longer survival time was, according to this study, treatment with the ADRIA-plus protocol. This treatment resulted in a significantly longer survival time than the treatment with prednisolone or doxorubicin alone. Further studies are needed to investigate if the above mentioned parameters are useful in prognostication in dogs with malignant lymphoma.